2005
DOI: 10.1111/j.1540-627x.2005.00139.x
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation and Impact of ISO 9000 among Small Manufacturing Enterprises

Abstract: Quality is essential to customer satisfaction and competitive success. Unfortunately, resource constraints can place the small-firm manufacturer at a quality disadvantage. This paper considers the benefits and barriers to International Standards Organization (ISO) 9000 certification among small-firm manufacturers. An empirical study explores whether small manufacturers can successfully implement and benefit from a standardized and resource-intensive program such as ISO 9000. The answer is yes if management can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
165
0
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(194 citation statements)
references
References 25 publications
9
165
0
11
Order By: Relevance
“…Por fim, as considerações finais sobre o programa de qualificação e os resultados da aplicação piloto são apresentados na seção 7. MOLINA-MORALES, 2008;WOLFE;NELLES, 2008). Devido às vantagens que os aglomerados podem trazer, tanto para as empresas como para o desenvolvimento regional, várias políticas públicas vêm sendo desenvolvidas, como, por exemplo, a experiência da Indonésia relatada por Tambunan (2005).…”
Section: E Jonker E Karapetrovic (2004)unclassified
See 1 more Smart Citation
“…Por fim, as considerações finais sobre o programa de qualificação e os resultados da aplicação piloto são apresentados na seção 7. MOLINA-MORALES, 2008;WOLFE;NELLES, 2008). Devido às vantagens que os aglomerados podem trazer, tanto para as empresas como para o desenvolvimento regional, várias políticas públicas vêm sendo desenvolvidas, como, por exemplo, a experiência da Indonésia relatada por Tambunan (2005).…”
Section: E Jonker E Karapetrovic (2004)unclassified
“…Em geral, a literatura que trata sobre a integração de sistemas de gestão distingue dois níveis de integração: alinhamento, no qual as similaridades entre as normas são utilizadas para estruturar o sistema, mas procedimentos separados para cada norma são mantidos; e integração, no qual ocorre a integração completa de procedimentos relevantes e instruções de trabalho (JORGENSEN; REMMEN; MELLADO, 2006;DALE, 2001 A implementação de um sistema de gestão da qualidade não contribui somente para o atendimento das necessidades dos clientes, mas também auxilia na prevenção de custos de retrabalho, desperdícios e outras fontes de ineficiências (KOC, 2007;SINGH, 2008). Um estudo empírico conduzido por Briscoe, Fawcett e Todd (2005), o qual envolveu pequenas empresas canadenses e americanas, concluiu que pequenas empresas podem implementar a certificação ISO 9001 e ganhar competitividade se estas estabelecerem uma cultura de qualidade e fizerem com que as práticas façam parte da rotina da empresa.…”
Section: Sistemas De Gestão Integradosunclassified
“…En efecto, como señalan Briscoe et al (2005), si las prácticas asociadas a ISO 9001 no se interiorizan a pesar de la implantación y certifi cación formal, entonces resulta difícil que tengan un efecto en el desempeño de las empresas.…”
Section: Tabla III (Cont) Principales Factores Evidenciados De Formaunclassified
“…The studies on internalization have also analyzed other drivers which might be considered in the future in order to explain other factors which might facilitate internalization, and thus an impact upon benefits. These other drivers which might play a role in the relationship between internalization and performance are the following (Briscoe et al, 2005;Naveh and Marcus, 2005;Christmann and Taylor, 2006;Singh, 2008): quality culture, leadership, pressure by stakeholders, innovation environment, and system coordination with suppliers and customers. These studies have shown that these drivers (that we can classify as internal and external drivers) may have positive effects on internalization.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…More recent studies have gone beyond this notion and analysed a heterogeneous adoption of the quality standards (Naveh and Marcus, 2004;Briscoe et al, 2005;Prajogo et al, 2012), that is, they have considered that those firms implementing a quality standard (e.g. the ISO 9001 standard), may develop its requirements in different ways (Nair and Prajogo, 2009;Boiral, 2011).…”
Section: Introductionmentioning
confidence: 99%